2005
DOI: 10.1258/002221505774783421
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal endoscopic repair of anterior skull-base fistulas: the Kuala Lumpur experience

Abstract: The purpose of this retrospective study is to determine the pattern of cerebrospinal fluid (CSF) rhinorrhoea presenting to our tertiary referral centre in Kuala Lumpur and to assess the clinical outcomes of endonasal endoscopic surgery for repair of anterior skull base fistulas. Sixteen patients were treated between 1998 and 2004. The aetiology of the condition was spontaneous in seven and acquired in nine patients. In the acquired category, three patients had accidental trauma and this was iatrogenic in six p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 24 publications
(64 reference statements)
1
54
1
1
Order By: Relevance
“…72,80 Various authors have successfully used different types of autologous and nonautologous grafts, such as a mucoperiosteal flap from the middle turbinate or septum or mucoperichondrial, osseous, cartilaginous, fat, muscular fascia, middle turbinate, or septum pedunculated graft, or any combination of these grafts. 1,3,11,13,15,22,[24][25][26]28,35,47,51,55,56,64,65,67,77,79,90,101,108 Another widely discussed issue in endoscopic transnasal repair is whether the grafts used for repair should be placed above (inlay) or beneath (onlay) the skull base defects. In a meta-analysis, Hegazy et al 53 found that both techniques yielded similar results.…”
Section: Surgical Managementmentioning
confidence: 99%
“…72,80 Various authors have successfully used different types of autologous and nonautologous grafts, such as a mucoperiosteal flap from the middle turbinate or septum or mucoperichondrial, osseous, cartilaginous, fat, muscular fascia, middle turbinate, or septum pedunculated graft, or any combination of these grafts. 1,3,11,13,15,22,[24][25][26]28,35,47,51,55,56,64,65,67,77,79,90,101,108 Another widely discussed issue in endoscopic transnasal repair is whether the grafts used for repair should be placed above (inlay) or beneath (onlay) the skull base defects. In a meta-analysis, Hegazy et al 53 found that both techniques yielded similar results.…”
Section: Surgical Managementmentioning
confidence: 99%
“…In experienced hands, it is possible to obtain better access to the orbital apex and even to decompress the optic nerve endoscopically [18]. Hypertrophy of the extraocular muscles and orbital fat in thyroid eye disease is one of the commonest causes of proptosis.…”
Section: Orbital Decompressionmentioning
confidence: 99%
“…Many operative techniques and different types of graft material have been described (10). The grafts described include a nasal mucosal flap, free graft of nasal mucosa which may be a composite graft incorporating turbinate bone, conchal or septal cartilage, temporalis fascia and fascia lata which may be supported by fat (11)(12)(13). All of these techniques give a good success rate.…”
Section: Discussionmentioning
confidence: 99%